THE IMAGE OF THATCHERISM IN TOP GIRLS BY CARYL CHURCHILL (American Journal of Research in Humanities and Social Sciences, 2022)
Caryl Churchill's Top Girls (1982) reveals how women have achieved a point of strength and independence in their battle to face men's oppression throughout history. Churchill has replicated recent transitions in the 1980s and 1990s in works that depict these movements' central concerns and contradictions as they change. Similarly, her theater is a result of many problems and shifts in hegemonic modes of production during this time. This paper traces the achievements of the major character of Top Girls, Marlene, in her way of life and her handling of the struggles of other women around her. Because of this strength, Marlene is compared to the British Prime Minister, Thatcher. Therefore, this paper will shed light on the term of Thatcherism and its application to the play with a reference to the continuing injustice of women through different aspects of culture and the new face of feminism, the Iron Woman.